Two Nonredundant SecA Homologues Function in Mycobacteria - Braunstein, Miriam (American Society for Microbiology, 2001)
The proper extracytoplasmic localization of proteins is an important aspect of mycobacterial physiology and the pathogenesis of Mycobacterium tuberculosis. The protein export systems of mycobacteria have remained unexplored. The Sec-dependent protein export pathway has been well characterized in Escherichia coli and is responsible for transport across the cytoplasmic membrane of proteins containing signal sequences at their amino termini. SecA is a central component of this pathway, and it is highly conserved throughout bacteria. Here we report on an unusual property of mycobacterial protein export—the presence of two homologues of SecA (SecA1 and SecA2). Using an allelic-exchange strategy in Mycobacterium smegmatis, we demonstrate that secA1 is an essential gene. In contrast, secA2 can be deleted and is the first example of a nonessential secA homologue. The essential nature of secA1, which is consistent with the conserved Sec pathway, leads us to believe that secA1 represents the equivalent of E. coli secA. The results of a phenotypic analysis of a ΔsecA2 mutant of M. smegmatis are presented here and also indicate a role for SecA2 in protein export. Based on our study, it appears that SecA2 can assist SecA1 in the export of some proteins via the Sec pathway. However, SecA2 is not the functional equivalent of SecA1. This finding, in combination with the fact that SecA2 is highly conserved throughout mycobacteria, suggests a second role for SecA2. The possibility exists that another role for SecA2 is to export a specific subset of proteins.